(untitled) (Palíndromo, 2023)
This article offers some reflections about the Armazém Project, including its historical, conceptual and artistic relations. The text addresses multiples and artist’s publications as the driving forces to the realization of the project in its various articulations and activities over more than 10 years of existence. The collective aspect of a project that becomes a living organism, the connection between artists of different generations and with the public, that questions the hierarchy established on the art field, all that related to the multiplicity of the work of art, results on a relational proposition, a vibrant and dynamic project in the history of the art of Santa Catarina state, in Brazil, with an insertion in the national’s art scene.